Qualified Immunity: State Power, Vigilantism and the History of Racial Violence. (October 2021) - Jacobs, Aaron
Abstract : Since the historic uprisings sparked by the murder of George Floyd, growing calls to defund the police have upended mainstream political discourse in the United States. Outrage at appalling evidence of rampant police brutality and an entrenched culture of impunity have moved to the very center of public debate what were until recently dismissed as radical demands. This dramatic shift has, among other things, opened up space for discussion of the history of policing and the prison-industrial complex more broadly. In particular, abolitionists have urged examination of the deep roots of our contemporary situation. As the organizer and educator Mariame Kaba argued in an editorial published in The New York Times, "There is not a single era in United States history in which the police were not a force of violence against black people." 1 That a statement like this would appear in the paper of record reflects a paradigm shift in popular understandings of the history of the criminal legal system.